A New Explanation of Why the Euthyphro Dilemma Is a False Dilemma - Søvik, Atle Ottesen (Religions, 2023)
The article gives a new explanation for why the Euthyphro dilemma is a false dilemma and argues that it is a middle position that both the theist and the atheist could accept. The argument is that both the will of God and the preferences of individuals are necessary truthmakers for what the good is. Each of the components is insufficient on its own, but jointly they are sufficient. Individual preferences are necessary to provide the normativity of the good, while God is necessary for the objectivity of the good. It is the combination of individual preferences into a possible world that is valuated the most by the most that gives the normative goal for moral choices. It is the knowledge of God of what would most probably be valuated the most by the most that makes a concrete choice the morally right thing to do in a concrete situation.